Persepsi Mahasiswa Ilmu Komunikasi Terhadap Gaya Retorika Pejabat Publik Saat Menjawab Pertanyaan Wartawan Melalui TikTok (Pada Akun @cnnindonesia) - I Dewa Ayu Agung Sauca Widiasari Putri; Jonathan Jacob Paul Latupeirissa (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2026)
This study examines Communication Studies students' perceptions of public officials' rhetorical styles when responding to journalists' questions on TikTok, specifically through the @cnnindonesia account. Grounded in rhetorical theory and audience perception frameworks within digital political communication, this research adopts a qualitative descriptive approach. Data were collected through in-depth interviews with two purposively selected informants: one Communication Studies lecturer with expertise in political communication and one undergraduate student who actively consumes political content on TikTok. Informants were selected based on specific criteria, including academic expertise and consistent media consumption habits. Data were analyzed using thematic analysis and triangulated through cross-referencing of interview responses and documentary evidence. The findings reveal that students perceive the rhetorical styles of many public officials as ineffective, characterized by unclear messaging, weak command of data, and defensive or illogical statements. These communication failures diminish student trust in public officials and highlight a disconnect between the demands of digital public communication and the rhetorical competencies of officials. This study contributes to the understanding of how rhetorical quality shapes political credibility in the TikTok era and offers practical implications for public communication training.